Motif Da’i Berdakwah di Kota Ambon - SULAEMAN SULAEMAN; IRTA SULASTRI (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2017)
This paper describes and explains the self experience of motive behind the preacher choosing to preach. Preaching experiences in Ambon City still get scorn, insult, ridicule from multicultural environment. Environment treats them with apathy, lack of acceptance, recognition, and less respected in preaching. The preacher conveys communication message of Islam, it is still not able to open mind and awareness, in fact, there are many muslims still follow their ancestor doctrines and cannot think crtically. Messages of religious communication should be communicated sympathetically and rationally. This research used subjective interpretive method with phenomenology approach. Researchers explored self experience preacher, conducted by using data collection through in-depth inter-views and participatory observation with supporting data based on social action perspective. The results showed that the subject interpreted himself choosing preacher as profession for reason and purpose motive in preaching communica-tion. Preacher communication action is not “single,” there is another phenom-enon shows the double motive of preaching, though the phenomenon is not likely to appear.